Structural shakedown: a new methodology for estimating the residual displacements - Liepa, Liudas; Blaževičius, Gediminas; Merkevičiūtė, Dovilė; Atkočiūnas, Juozas (Journal of Civil Engineering and Management, 2016)
A vector of residual forces of the ideally elastic-plastic structure at shakedown is obtained by solving the static analysis problem. A unique distribution of the residual forces is determined if the analysis is based on the minimum complementary deformation energy principle. However, the residual displacements developing in the shakedown process of ideally elastic-plastic structures under variable repeated loads can vary non-monotonically. Nevertheless mathematical models for the optimization problems of steel structures at shakedown must include the conditions for strength (safety) and stiffness (serviceability). Residual displacements determined by the plastic deformations are included in the stiffness conditions; therefore to improve the optimal solution it is necessary to determine upper and lower bounds of the residual displacement variations. This paper describes an improved methodology for estimating the variation bounds of the residual displacements at shakedown.